Self Interpretation: The Identity of Women Legislator - Nur'annafi Farni Syammaella; Farida Farida; Harliantara Harliantara; Witanti Prihatiningsih (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
There is an expansion of the meaning of women's personal identities in the process of transforming the contestation of political life in Indonesia. This research is able to interpret the role and position of women in determining the direction of changing women's identity. Methodologically, this research uses a Schutz phenomenological approach through in-depth interviews. Field research was carried out by taking research subjects, comprising eight female members of the legislature in the city of Surabaya. The results of the study revealed women's identity as a form of approved self-meaning: first, women’s identity as a female fighter. This identity offers a form of identity as part of tracking the struggle of gender fighters. The second is women’s identity as a people's fighters. The third is the identity of a great woman who has electability and credibility as people's representatives. The fourth is women’s identity as a superwoman. They stand to fight for their family’s welfare, a manifestation of the excessive burden of the domestic role that is their husband’s responsibility. The most powerful factors forming women's legal identity are family, political parties, community views and political interests. Many "women legislators" in Indonesia are still developing themselves and adapting to the modernization of political identity. In conclusion, the direction of identity change through self-definition is incompatible with the direction of progressive political change in political communication competence. The significance of this research will give an impact on the political system regarding the recruitment and regeneration process of legislative candidates in Indonesia in the future.